TEORI KONSELING (SUATU PENDEKATAN KONSELING GESTALT) - KHOLIFATUL HASANAH (Universitas Islam Negeri Mataram, 2016)
Every human being must have problems, whether those problems as the implications in addressing a less conducive environment and personal environment who could not afford to be organised so that resulted in the birth of the abnormal behaviors. Gestalt counseling approach wanted to improve individuals by focusing on the present perspective, through the projection of the past phenomenon with the present condition. The effectiveness of the collaboration between counselors and conselee largely determine the success in counseling process, because it emphasized on personal attitude of the counselee in resolving their problems, meanwhile, couselorsare only in charge of transforming knowledge and assist the counselee in fnding the rootof the problem moreover to help the counselee to fnd the way to resolve their problems.